2020
DOI: 10.2174/1871526519666190716121824
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Infections of Wild Boars (Sus scrofa) in Iran: A Literature Review

Abstract: Background: Swine species are important source for meat production worldwide, except in Islamic countries where pig breeding and pork consumption are forbidden. Hence, they are often neglected in these regions. A considerable number of wild boars (Susscrofa) inhabit Iranian territories, particularly in dense forests of north, west and southwest of the country, but our knowledge on their parasites is very limited. Objective: The lack of a comprehensive record in this connection encouraged us to review the wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The tapeworm T. s o l i u m is a cosmopolitan parasite with global distribution, with most human cases found in Latin America, Asia, and Africa alongside emergence in recent years in the USA and Europe [9]. In addition to widespread E. granulosus, recently E. multilocularis has become very important because of its expansion from endemic areas to nonendemic areas in North America, Europe, and Japan, apparently by a displacement of fox populations [10]. Regarding Trichinella spp., during the period 1986-2010, 65,818 new cases were registered in 41 countries.…”
Section: Zoonotic Parasitoses In Humans and Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tapeworm T. s o l i u m is a cosmopolitan parasite with global distribution, with most human cases found in Latin America, Asia, and Africa alongside emergence in recent years in the USA and Europe [9]. In addition to widespread E. granulosus, recently E. multilocularis has become very important because of its expansion from endemic areas to nonendemic areas in North America, Europe, and Japan, apparently by a displacement of fox populations [10]. Regarding Trichinella spp., during the period 1986-2010, 65,818 new cases were registered in 41 countries.…”
Section: Zoonotic Parasitoses In Humans and Animalsmentioning
confidence: 99%
“…Regarding Trichinella spp., during the period 1986-2010, 65,818 new cases were registered in 41 countries. Of these, 87% occurred in Europe associated with boar consumption [10]. Characteristics of selected, most important zoonotic parasitoses are shown in Table 1 Fascioliasis is caused by parasites of the genus Fasciola.…”
Section: Zoonotic Parasitoses In Humans and Animalsmentioning
confidence: 99%
“…There are few studies on the infection of wild boars with protozoans and helminths in Iran, though wild boars are known to be reservoir hosts for some important parasites (Solaymani-Mohammadi et al, 2005;Maleki et al, 2019). This study has shown that there is a lack of information about protozoan infections in these animals in Iran, and xx xx further study is required by Iranian health authorities and veterinary organizations to identify wild boar parasites and investigate the role of these parasites in the health of wild boar herds and also in public health.…”
Section: Discussionmentioning
confidence: 99%
“…Protozoans that may be transmitted from boars to human are mainly Balantidium coli, Entamoeba polecki, Blastocystis, Giardia, Cryptosporidium, and Toxoplasma gondii, (Yaghoobi et al, 2016). However, due to food habits and religious advice for Muslims) pig breeding and pork consumption are forbidden, (these xx xx diseases are less significant in these communities (Maleki et al, 2019).…”
mentioning
confidence: 99%
“…Khalilzadeh et al, 2016; Ashrafzadeh et al, 2018), and although the focus has been on S. scrofa as a source of zoonotic infections (e.g. Maleki et al, 2020), knowledge of Iranian wild pigs has nevertheless improved. Thus, in conclusion, although we realize that the attention received by our article on Iranian Suidae does not reflect genuine conservation science interest in either pigs or Iran, we appreciate the opportunity it has given us to highlight these important conservation topics.…”
mentioning
confidence: 99%